ONLINE EDUCATION VS TRADITIONAL EDUCATION. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article compares online education and traditional face-to-face education, focusing on their effectiveness, advantages, and limitations. Online education offers flexibility, accessibility, and technological integration, while traditional education provides direct interaction, structured learning environments, and immediate feedback. The study analyzes how both educational models influence students’ academic performance, engagement, and learning outcomes. The findings aim to identify the most effective approaches to meet the diverse needs of modern learners.